Keterkaitan Iklim Organisasi dengan Faktor lainnya - Sisy Maharani; Hadiyanto Hadiyanto; Rusdinal Rusdinal; Sulastri Sulastri (Universitas Negeri Padang, 2021)
This research was made to determine what factors are influenced by organizational climate and what factors affect organizational climate. Factors influenced by organizational climate: 1) job satisfaction, 2) employee performance, 3) work motivation. Factors that influence organizational climate: 1) leadership style, 2) organizational culture, 3) work culture, 4) interpersonal communication, 5) commitment. Sources of data from this research are taken from journal articles, theses and supported by books related to organizational climate.